Successful management of a patient with sudden loss of vision and eclampsia complicated by posterior reversible encephalopathy syndrome - Vaswani, Babita; Gopal, Sriram; Satia, Meena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Reversible visual disturbances in patients with eclampsia may be due to either retinal detachment or retinal arteriolar vasospasm or thrombosis of the central retinal arteries or PRES (posterior reversible encephalopathy syndrome). Although retinal arteriolar vasospasm is the most common mechanism of visual disturbance, cortical blindness may occur in 1% to 15% of patients with eclampsia. Reporting herewith a case of reversible cortical blindness in the setting of severe preeclampsia complicated with eclampsia.